Difração de ondas eletromagnéticas em um condutor perfeito cilíndrico - PIRES, Andrey Viana (2018)
This work aims to analyze the effects caused by diffraction in the propagation of signals in mobile communications. Through simulations, the studies presented will expose how the obstruction caused by a perfect conductor cylinder affects the propagation of electromagnetic waves in various operating frequency levels and how it will affect receptors that travels across it’s shadow zone, aiming to provide approximate data to the preparation of mobile communication systems.It will need detailed knowledge about the electromagnetic wave propagation mechanisms, programming skills and physical and mathematical basis for the calculation of the fields involved in the processes of the simulations. The results will be presented in forms of charts and graphs for comparison purposes between the various operating frequencies of mobile communication systems, as well as variations in the source position relative to the obstruction.